CHANGES OF VIEWPOINTS IN INDONESIAN-ENGLISH TRANSLATION - Susini Made; Sujaya Nyoman (Universitas Warmadewa, 2021)
This study concerns with translation which involves languages that have different linguistic and cultural systems. When a source and target language do not have the same system of language and culture, to some extent, equivalence cannot be directly achieved. By deploying Vinay & Darbelnet’s Modulation (1995) and House’s translation equivalence (2015), this study is to reveal the changes of point of view the translators did in translating texts from Indonesian into English. The data sources of this present study include Indonesian novels and short stories loaded with culture and their English translations. The analysis revealed that to create adequate target texts, the translators changed their points of view through some conditions. The changes include: a) negation of opposite; b) part for the whole; c) abstract for concrete; d) cause for effect; e) active for passive; f) space for time; g) change of symbols; and h) intervals and limits. Changing point of view becomes cultural bridge in the translation which involves languages with different culture.